Konsep Makkîyah dan Madanîyah dalam Studi Hadîth: Menggagas Pemetaan Kronologis Hadîth Nabawî - Nirwana, Dzikri (Program Pascasarjana UIN Sunan Ampel Surabaya, 2008)
The QurâÃ¢nic Studies have long recognized the conceptual dichotomy of MakkÃ®yah and Madaniyah where verses are classified as either belonging to the period of Makkah or Madinah. This paper suggests that this conceptual dichotomy may also be applied in the study of the science of the prophetic saying (hadÃ®th). We propose that paradigm of the QurâÃ¢nic Studies concerning the periodical distinction may be borrowed to understand and classify the prophetic sayings along the line of MakkÃ®yah and MadanÃ®yah. The paper however acknowledges this effort is not without methodological difficulties. There are hadÃ®th that may âin terms of their characteristics and substance- be regarded as MakkÃ®, but may also be considered as Madani because they are narrated by the people of Madinah (the AnsÃ¢r). To tackle this problem, we propose double-way strategy. We will first find out which hadÃ®ths are regarded as MakkÃ® in terms of their characteristics and substance, and then examine the idea of what many have called the âargumentation of the prophetic termâ. The first is about the thematic study, while the second is about the analysis of the term of a hadÃ®th. The first will involve the consultation of mainly the hadÃ®th authoritative book called MiftÃ¢h KunÃ»z al-Sunnah, while the second will consult those books that employ the personal-encyclopedic approach including books of hadÃ®th, the sciences of the QurâÃ¢n (tafsÃ®r), the reason of revelation (asbÃ¢b al-nuzÃ»l), the reason of decreeing (asbÃ¢b al-wurÃ»d), and the autobiography of the prophet (sÃ®rah). The meaning of a hadÃ®th and its appropriation in these books will be analyzed in the light of the science of hadÃ®th. The paper will examine how different scientists of tafsir, hadÃ®th and so on would understand and interpret the same hadÃ®th.